1991
DOI: 10.1083/jcb.112.2.245
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a membrane glycoprotein found primarily in the prelysosomal endosome compartment.

Abstract: Abstract. Cells contain an intracellular compartment that serves as both the "prelysosomal" delivery site for newly synthesized lysosomal enzymes by the mannose 6-phosphate (Man6P) receptor and as a station along the endocytic pathway to lysosomes. We have obtained mAbs to a *57-kD membrane glycoprotein, (called here plgp57), found predominantly in this prelysosomal endosome compartment. This conclusion is supported by the following results: (a) plgp57 was primarily found in a population of late endosomes that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

1991
1991
2012
2012

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 48 publications
1
7
0
Order By: Relevance
“…We found that this antigen was highly expressed in the TC, including phagolysosomes ; it was undetectable, or present at low levels, in the plasma membrane, early endosomes, carrier vesicles, and lysosomes. This distribution resembles that of a 57-kD membrane glycoprotein recently reported to be predominantly in the PLC/late endosomes ofbovine cells (Park et al, 1991).…”
Section: Macrosialin As a Marker Fbr Plcsupporting
confidence: 80%
“…We found that this antigen was highly expressed in the TC, including phagolysosomes ; it was undetectable, or present at low levels, in the plasma membrane, early endosomes, carrier vesicles, and lysosomes. This distribution resembles that of a 57-kD membrane glycoprotein recently reported to be predominantly in the PLC/late endosomes ofbovine cells (Park et al, 1991).…”
Section: Macrosialin As a Marker Fbr Plcsupporting
confidence: 80%
“…To identify the transport pathway mediated by the purified vesicles, we examined the cargo content of the purified vesicles. As judged by immunoblotting, the purified vesicles lacked Sec61βp [ER marker, (25)], giantin [Golgi marker, (26)], mannose‐6‐phosphate receptor [M6PR, late endosome marker, (27)], lamp‐1 [lysosome marker, (28)], and sodium/potassium (Na + /K + ) ATPase [plasma membrane marker, (29)] (Figure 9A). In contrast, the purified vesicles contained a significant level of transferrin receptor, suggesting that these vesicles were derived from the early endosome (Figure 9B).…”
Section: Resultsmentioning
confidence: 99%
“…The steady state amount of both these transient markers within this compartment is negligible. Future efforts will be directed toward the identification of integral membrane proteins associated with the prevacuolar endosomal compartment to serve as functional markers like the recently identified 57-kD protein of the mammalian prelysosomal compartment (Park et al, 1991). Interestingly, the density of this organelle in yeast (",,1.12 g/ml) is nearly identical to the density of the mammalian prelysosomal compartment (Mullock et al, 1989;Park et al, 1991).…”
Section: Discussionmentioning
confidence: 99%